Mako surgical robot could improve the traditional surgical techniques of joint surgery fellows - Cheng Wang; Yang Li; Jiazheng Chen; Minwei Zhao; Xinguang Wang; Feng Li; Hua Tian (BMC Medical Education)
Abstract Background With the increasing incidence of joint diseases and the growing demand for surgical precision, robotic-assisted surgery has emerged as a promising advancement in orthopedic training. The Mako surgical robot, known for its precision in preoperative planning and intraoperative guidance, may offer significant educational benefits to joint surgery fellows. However, its potential impact on enhancing traditional surgical skills and research capabilities remains underexplored. Objective To evaluate whether systematic training in Mako robotic-assisted hip replacement improves surgical performance and research skills among joint surgery fellows compared to traditional training. Methods From October 2021 to May 2023, 40 joint surgery fellows were randomly divided into two groups, the experimental group received a comprehensive and systematic mako robot-assisted hip replacement training course. The control group received traditional training in hip replacement surgery within one month. The results of operation simulation and questionnaire were used to evaluate the training effect. Results The test results showed that in the simulation test of acetabular prosthesis placement, the overall pass rate of the experimental group was 90%, and that of the control group was 60%(p = 0.028). The results of the questionnaire showed that in clinical aspects, the score of surgical skill growth in the experimental group was higher than that in the control group after training [(10.9 ± 3.6) score vs. (4.4 ± 1.6) score, P < 0.001]. In terms of scientific research, the experimental group obtained more scientific research skills and abilities than the control group after training [(43.7 ± 1.9) vs. (25.0 ± 3.2) points, P < 0.001]. Conclusion The Mako orthopedic robot system enables joint surgery fellows to improve the traditional surgical techniques and the capacity for scientific research.